FOUR NEW VARIABLE STARS NEAR CL AURIGAE. II - Kim, Chun-Hwey; Lee, Jae Woo; Kim, Duck Hyun; Andronov, I. L. (Одеські астрономічні публікації, 2010)
We report on a discovery of four new variable stars (USNO-B1.0 1234-0103195, 1235-0097170, 1236-0100293 and 1236-0100092) in the field of CL Aur. The stars are classified as eclipsing binary stars with orbital periods of 0.5137413(23) (EW type), 0.8698365(26) (EA) and 4.0055842(40) (EA with a significant orbital eccentricity), respectively. The fourth star (USNO-B1.0 1236-0100092) showed only one partial ascending branch of the light curves, although 22 nights were covered at the 61-cm telescope at the Sobaeksan Optical Astronomy Observatory (SOAO) in Korea. Fourteen minima timings for these stars are published separately. In an addition to the original discovery paper (Kim et al. 2010), we discuss methodological problems and present results of mathematical modeling of the light curves using other methods, i.e. trigonometric polynomial fits and the newly developed fit “NAV” (”New Algol Variable”).